An improved exponential stability criterion and distributed H∞ filter design for spatially interconnected discrete-time systems with time-varying delay. Issue 3 (4th March 2023) - Wang, Hui; Xu, Huiling; Chen, Xuefeng; Zhang, Dan
Abstract : This paper proposes an improved exponential stability analysis criterion and designs a distributed H ∞ filter for a spatially interconnected discrete-time time-varying delay (SIDTD) system. Firstly, combining the Wirtinger-based inequality with reciprocally convex combination inequality, a new and less conservative exponential stability criterion, which guarantees the well-posedness, exponential stability, and H ∞ performance of the SIDTD system, is reduced to standard linear matrix inequalities. Moreover, we design a distributed structure-preserving H ∞ filter based on the new stability result. The structure-preserving H ∞ filter and the delay-free H ∞ filter can be obtained by employing the Finsler lemma. Finally, the validity and advantages of the derived results are shown by a numerical example and a practical example.